Rancang Bangun Sistem Informasi Manajemen Konferensi Ilmiah Berbasis Web - Darma Kotama, I Nyoman; Sudarma, Made; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 4 No 2 (2017): Jurnal SPEKTRUM, 2018)
This paper is projecting website system built on top of PHP Framework Laravel 5.2 and MySQL DBMS which contains 6 modules of scientific conference management needs, Master Conference, User Management, Submission, Website Management, Schedule, and Post Conference. From the development and testing system with Black Box method concluded that the system is running well and feasible to be applied to the management of the conference in Electrical Engineering Program Faculty of Engineering Udayana University.